Social Media As A Catalyst For Future Terrorist Recruitment: A Bibliometric Analysis of Emerging Trends And Countermeasures: Media Sosial sebagai Katalisator Rekrutmen Teroris di Masa Depan: Analisis Bibliometrik Tren yang Muncul dan Langkah-Langkah Penanggulangan - May May Maysarah; Reyhan Fakhreja; Asep Adang Supriyadi (Universitas Negeri Semarang, 2025)
This study addresses the growing challenge of terrorist recruitment and radicalization via social media by mapping scholarly activity and thematic evolution in this field. Its objective is to identify publication trends and key research themes related to digital extremism from 2015 to 2025. We conducted a bibliometric analysis of 416 Scopus-indexed articles, employing VOSviewer and Bibliometrix to generate co‑occurrence networks and thematic evolution maps. Results reveal a marked increase in research output since 2017 peaking in 2020 amid heightened online engagement during the COVID‑19 pandemic and a geographic concentration of authorship in the United States and the United Kingdom, with limited contributions from regions most affected by terrorism, such as the Middle East and Southeast Asia. Thematic analysis indicates a shift from early studies on propaganda dissemination (2015–2018) to advanced examinations of algorithmic radicalization, AI‑enabled recruitment, encrypted coordination, and emerging threats like deepfake propaganda (2019–2025). We conclude that effective countermeasures require proactive, multidisciplinary strategies, including community‑based interventions targeting socio‑psychological vulnerabilities, cross‑platform regulatory cooperation, and AI‑driven content moderation. This framework underscores the necessity of integrating technological, psychological, and policy perspectives to counter evolving digital radicalization.